2022
DOI: 10.1186/s12891-022-05766-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-operative carbohydrate loading in femur fracture: a randomized controlled trial

Abstract: Background Femur fracture is a major burden among elderly people, leading patients to be bedridden for a long time in the hospital. The body is more likely to be in a catabolic state as a result of the prolonged fasting period required for surgery, leading to an increase in insulin resistance. Pre-operative carbohydrate loading has been shown to improve postoperative outcomes in several countries. The study aimed to evaluate the effect of pre-operative carbohydrate loading in femur fracture sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Eight studies reported postoperative scores of pain scores using a VAS, with data available on 739 participants ( 29 , 35 , 44 , 62 , 67 70 ). The results found no statistically significant difference after surgery ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported postoperative scores of pain scores using a VAS, with data available on 739 participants ( 29 , 35 , 44 , 62 , 67 70 ). The results found no statistically significant difference after surgery ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon confirmation of a participant's eligibility, the next envelope in the sequence was opened, and the treatment allocation was entered on a randomization list. A similar procedure of randomization technique was used in the previous study [62].…”
Section: Randomizationmentioning
confidence: 99%
“…The VAS consisted of a 10 cm straight line with the endpoints defining the intensity of pain from zero to 10 indicating that zero indicated "no pain at all" and 10 indicated "worst pain". They were asked to express their severity of pain at the time of data collection in a descriptive term as no pain, mild pain, moderate pain, severe pain, or worst pain, and they were ranked to numerical scores for analysis [62]. Another outcome was the plantar fascia thickness which was assessed before intervention (baseline) and after intervention at six months through high-resolution ultrasonography (Ultrasound machine-SONOACE X7) by a trained radiologist.…”
Section: Study Variables Outcome Variablesmentioning
confidence: 99%
“…A large number of ERAS protocols along with the European Society for Parental and Enteral Nutrition (ESPEN) guidelines have also recommended the consumption of a carbohydrate-rich drink the night before and 2 hours prior to the surgical procedure to reduce insulin resistance and improve hunger perioperatively in patients undergoing general surgery 66,68 . However, the results of preoperative carbohydrate loading in patients undergoing orthopaedic surgery have been mixed 69,70 . Postoperatively, early resumption of enteral intake is recommended along with the continuation of a protein-rich diet through early rehabilitation.…”
Section: Modifying Nutritionmentioning
confidence: 99%